Consideration by investigating judge of the complaints of omission of investigator or prosecutor lying in the failure to introduce information on a criminal offense in the course of pretrial investigation: issues of law enforcement and ways of solutions - Шапутько, С.В (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
The article deals with the comparative analysis of legislation, theoretical researches as well as court practice on considering by investigating judge of the complaints of omission of investigator or prosecutor lying in the failure to introduce information on a criminal offence to the Unified Register of Pretrial Investigations. Based on the analysis of decrees of the investigating judges on the complaints of actions or omissions of investigator or prosecutor it was found that court practice on determination of the term for lodging the complaint of omission of investigator or prosecutor lying in the failure to introduce information to the URPR is contradicting. In one case the court finds that the term for lodging complaints of omission of investigator or prosecutor lying in failure to introduce information to the URPR starts within 24 hours of lodging the complaint of the criminal offense, and in other case from the moment when the person became familiar with the failure to introduce information to the URPR.Based on the above it is proposed to adopt in terms of legislation that calculation of the terms of lodging the complaint of omission shall be made starting next day after the term specified by the Criminal Procedure Code of Ukraine for carrying out by investigator or prosecutor of a particular action.It was found that it is problematic to complain omission of investigator or prosecutor if the decision of the investigator is made in the form other than provision as long as in this case the decision is to be drawn up in the form of the URPR extract. Based on the above it is proposed to resolve the issues on the term for lodging the complaint of omission of investigator or prosecutor in different ways.Based on the system analysis of court decisions of the judges of the first and appellate instance, legislation and scientific attitudes the author proposed to amend paragraph 1 of Article 304 of the Criminal Procedure Code of Ukraine as follows: «Complaints of the decisions, actions or omissions of investigator or prosecutor provided for by paragraph 1 of Article 303 of this Code shall be lodged by a person within ten days from the moment of decisions making, action or omission. If the decision of investigator or prosecutor is drawn up in the form of provision the term for lodging the complaint shall start from the date of receipt of its copy by a person. If in case of the decision of investigator or prosecutor the resolution is not prescribed, the complaint of their actions or omission shall be lodged within ten days starting next day after the end of the term determined for its carrying out by this Code»

Проведено порівняльний аналіз законодавства, теоретичних досліджень, а також судової практики щодо розгляду слідчим суддею скарг на бездіяльність слідчого або прокурора, яка полягає у невнесенні відомостей про кримінальне правопорушення до Єдиного реєстру досудових розслідувань. Запропоновано наукову позицію щодо визначення моменту закінчення строку подання скарги означеної категорії, передбаченої частиною першою ст. 304 КПК України, та відповідні зміни до КПК України
РОЗГЛЯД СЛІДЧИМ СУДДЕЮ СКАРГ НА БЕЗДІЯЛЬНІСТЬ СЛІДЧОГО АБО ПРОКУРОРА, ЯКА ПОЛЯГАЄ У НЕВНЕСЕННІ ВІДОМОСТЕЙ ПРО КРИМІНАЛЬНЕ ПРАВОПОРУШЕННЯ ПІД ЧАС ДОСУДОВОГО РОЗСЛІДУВАННЯ: ПРОБЛЕМИ ПРАВОЗАСТОСУВАННЯ ТА ШЛЯХИ ЇХ ВИРІШЕННЯ
Keywords: investigating judge; omission; investigator; prosecutor; pretrial investigation; complaint; criminal offense; term; complaint return; end of the term; слідчий суддя; бездіяльність; слідчий; прокурор; досудове розслідування; скарга; кримінальне правопорушення; строк; повернення скарги; закінчення строку